Phenotype Diversity and Gene Myostatin (MSTN) of Bangkok Chicken using PCR-RFLP - Triana Mardiah; Depison Depison; Helmi Ediyanto (Buletin Peternakan, 2021)
This study aims to characterize the phenotype and determine the diversity of the Myostatin (MSTN) gene at Bangkok chickens using the Polymerase Chain Reaction- Restriction Fragment Length Polymorphism (PCR-RFLP) method. This study used 50 Bangkok chicken blood samples taken from the axillary vein on the wing. DNA was extracted using the protocol Genomic DNA Purification Kit from Promega and then amplified by PCR (polymerase chain reaction) using a pair of primers F: 5'GGT TTT GAC GAC ATG AGC CT3' R: 5'CAG GTG GAA TGT CAT GCA GA3' with product length 955 bp. Amplification products were cut using restriction enzyme MboI with cutting site ↓GATC. MSTN|MboI fragments of the Bangkok chicken were electrophoresed using 2% agarose gel and visualized using doc gel. The average difference test (T-test) on body weight and weight gain of Bangkok chickens from DOC to 3 months by gender. Polymorphism analysis includes allele frequency and genotype. Male and female Bangkok chickens have low phenotype diversity. The MSTN|MboI gene fragment is monomorphic with band positions of 492 bp, 244 bp, and 219 bp resulting in a genotype of ++, and there is one type of allele with a + allele frequency of 100%.